The space between us: A self-managing approach to the creation of flexible spaces in Tsako Thabo Secondary School, South Africa - Dion-Barbin, Naïna (My University, 2023)
South Africa has made significant investments in education, with a portion of its GDP spent on education among the highest in Africa at 18.42% in 2021. However, the legacy of Apartheid is still felt, with a divided education system between Black and White students resulting in significant gaps in learning outcomes. For instance, only 5.3% of Black African students are enrolled in higher education compared to 24.6% for White students. This thesis explores the potential of collaborative spaces managed by learners from disadvantaged backgrounds to foster ownership and responsibility for their education. This self-management approach is a way to allow flexibility in the spaces and encourage the act of commoning in a context where cultural differences are deeply ingrained. The methodology was developed in partnership with the Tsako Thabo Secondary School in Mamelodi, Pretoria, through a co-design approach primarily involving students between the age of 14 to 18 years old as the managers of the space. Through this approach, students can develop a sense of ownership and responsibility over time. Based in Pretoria, South Africa, this research directly addresses real issues and engages with learners to provide a safe and inclusive environment where they can thrive. Since I believe architecture is beyond the physical space, the result of this study consists of three different components: a design proposal of the space, a new learner’s body structure with an executive committee to enable a self-managing approach, and a plan for financing the space. The room reflect the values of the learners and provide them new opportunities to develop as young adults. The study aims to create a safe space for learners from disadvantaged backgrounds, where they feel a sense of belonging and agency. The space between each one of us can be tremendous, or it can be as a simple centimetre depending on how we decide to look at the world. We are all unique, but I believe that by finding that space that unites us, we become stronger and achieve greater moments.
Keywords: Collaboration; Decentralization; Lifelong learnings; Flexible space; Self-management